In-plane behaviour of rubble stone masonry walls: experimental, numerical and analytical approach - Pereira, João Miguel (2021)
Unreinforced masonry construction is predominant in many urban areas world-wide. Many of these constructions are vulnerable to earthquakes, which are the main cause of damage and loss of cultural heritage. Understanding the in-plane behaviour of masonry walls when subjected to horizontal loadings will improve the society capacity to preserve and protect this cultural heritage. An experimental campaign on rubble stone masonry walls under different loading conditions is presented. This experimental campaign allows calibrating non-linear numerical models used to study these elements in a more comprehensive way, performing parametric studies regarding the geometry, pre-compression level, boundary conditions and mechanical properties. The capacity to estimate the shear strength using available analytical models is also reviewed, applied and compared.